Neuropsychiatric SLE: from animal model to human. (April 2017) - Pikman, R; Kivity, S; Levy, Y; Arango, M-T; Chapman, J; Yonath, H; Shoenfeld, Y; Gofrit, S G
Animal models are a key element in disease research and treatment. In the field of neuropsychiatric lupus research, inbred, transgenic and disease-induced mice provide an opportunity to study the pathogenic routes of this multifactorial illness. In addition to achieving a better understanding of the immune mechanisms underlying the disease onset, supplementary metabolic and endocrine influences have been discovered and investigated. The ever-expanding knowledge about the pathologic events that occur at disease inception enables us to explore new drugs and therapeutic approaches further and to test them using the same animal models. Discovery of the molecular targets that constitute the pathogenic basis of the disease along with scientific advancements allow us to target these molecules with monoclonal antibodies and other specific approaches directly. This novel therapy, termed "targeted biological medication" is a promising endeavor towards producing drugs that are more effective and less toxic. Further work to discover additional molecular targets in lupus' pathogenic mechanism and to produce drugs that neutralize their activity is needed to provide patients with safe and efficient methods of controlling and treating the disease.